2011
DOI: 10.1177/004005991104300305
|View full text |Cite
|
Sign up to set email alerts
|

Supporting School-Based Response to Intervention: A Practitioner's Model

Abstract: What are the key issues in leading school-based response to intervention (RTI) efforts? Several key components are essential to successfully implementing an RTI model in schools. RTI is an evolving practice; a school-based collaborative consultation RTI model offers a process that enables a school to apply RTI principles to its unique setting and concerns. Three schools in the Western United States implemented this RTI model with success, and their experience offers some guidelines and direction to school-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Two important inferences about the implementation of RtI are drawn from these state initiatives: (a) RtI models may be successfully implemented in schools to meet the needs of struggling learners, and b) RtI models assume different identities and formats across different schools and districts. These differences are due, in part, to the notion that each school district is unique and that RtI is described in many different ways (Hoover & Love, 2011). Although the majority of evidence supporting the use of RtI models has been conducted in the area of reading, increasing attention is being paid to the area of mathematics, as the realization that students who struggle with reading often also struggle with mathematics as well.…”
mentioning
confidence: 99%
“…Two important inferences about the implementation of RtI are drawn from these state initiatives: (a) RtI models may be successfully implemented in schools to meet the needs of struggling learners, and b) RtI models assume different identities and formats across different schools and districts. These differences are due, in part, to the notion that each school district is unique and that RtI is described in many different ways (Hoover & Love, 2011). Although the majority of evidence supporting the use of RtI models has been conducted in the area of reading, increasing attention is being paid to the area of mathematics, as the realization that students who struggle with reading often also struggle with mathematics as well.…”
mentioning
confidence: 99%
“…RTI can be used both as a formal system for providing interventions to students who are struggling (Hoover & Love, 2011) and as a procedure for identifying students with LD (Zirkel & Thomas, 2010). Within an RTI model, the intensity of instructional interventions increases as students advance through a series of tiers.…”
Section: Rtimentioning
confidence: 99%
“…Due to RTI, a significant change in structure and roles takes place between the classroom teacher and special educator (Bean & Lillenstein, 2012;Shepard & Salembier, 2010). Teachers who work together in the same classrooms need regularly scheduled opportunities to collaborate on student performance, curriculum preparation, and instructional practices (Hoover & Love, 2011). With special educator staff working with at-risk students, they will be helpful if the issue of special education eligibility arises because they have direct contact and working knowledge of the student's performance and needs (Burns & Gibbons, 2012;Hoover & Patton, 2008).…”
Section: Change In School Organizations Due To Response To Interventionmentioning
confidence: 99%
“…The initial implementation of RTI models into schools focused on three factors: collaborative structures, professional development, and leadership . Teacher buy-in was one of the most significant challenges for principals (Hoover & Love, 2011). White et al (2012) suggested that "schools will only be successful with the implementation of RTI if it includes district support, strong school leadership, teacher leadership and buy-in, and clear decision-making and communication" (p. 76).…”
Section: School Cultural Factorsmentioning
confidence: 99%
See 1 more Smart Citation